Particle Crushing Effect on The Geotechnical Properties of Soil - Rind, T. A.; Karira, H.; Jhatial, A. A.; Sohu, S.; Sandhu, A. R. (Engineering, Technology & Applied Science Research, 2019)
Foundations are considered as the backbone of a structure. Most of the times, the foundation is laid on the soil. For the foundation design of any structure, we need to know beforehand the soil conditions such as shear strength and permeability. These parameters help us determine the bearing capacity of the soil. The soil conditions are determined by performing various laboratory tests such as shear box test or tri-axial shear test. However, we cannot design the foundation considering these data as the ground conditions will change once the loads are applied to the soil as there are some soil particles with angularity or sharp edges will break. Once they will break, soil conditions will not remain the same as they were before since the gradation will change. This work is carried out in order to know the impact soil breakage brings to the soil (granular soil). For this purpose, actual ground conditions were simulated in the laboratory by applying one-dimensional compression to soil particles for about 45 minutes in a Universal Testing Machine (UTM). Different crushing loads to soil particles were applied and the change in the soil behavior was monitored. It was found that due to particle breakage of soil, the engineering properties of sand altered. This research work aims to analyze the effect of particle breakage only in the case of sand.